Nanomechanical DNA origami 'single-molecule beacons' directly imaged by atomic force microscopy - Kuzuya, Akinori (Nature Pub. Group, 2011)
DNA origami involves the folding of long single-stranded DNA into designed structures with the aid of short staple strands; such structures may enable the development of useful nanomechanical DNA devices. Here we develop versatile sensing systems for a variety of chemical and biological targets at molecular resolution. We have designed functional nanomechanical DNA origami devices that can be used as 'single-molecule beacons', and function as pinching devices. Using 'DNA origami pliers' and 'DNA origami forceps', which consist of two levers ~170 nm long connected at a fulcrum, various single-molecule inorganic and organic targets ranging from metal ions to proteins can be visually detected using atomic force microscopy by a shape transition of the origami devices. Any detection mechanism suitable for the target of interest, pinching, zipping or unzipping, can be chosen and used orthogonally with differently shaped origami devices in the same mixture using a single platform.